ANALISIS FISIOLOGIS TANAMAN JARAK PADA BERBAGAI TINGKAT PEMANGKASAN - Abdullah Sarijan (Universitas Musamus, Merauke, Papua, 2011)
Increased imports of oil and world oil prices expected to encourage the use of biodiesel as an alternative source of solar energy and fuel. Bio-diesel is one option to be used as an oil substitute energy sources. Bio-diesel can be made from biological sources or biomass, such as jatropha. Problems encountered in the development of distance is the lack of understanding of plant cultivation for farmers, especially in terms of pruning the plants. Pruning aims to establish a framework of generative growth of vegetative growth towards a more productive so that the amount of fruit obtained per plant more and more productive. The experiment was conducted at Gowa regency Parangloe which lasted from Marth until June 2009. The results showed that the treatment plant pruning distance effect on the number of branches, number of panicle, number of fruits per panicle, number of fruit per plant, number of fruit per plot, number of ripe fruit, seed number per fruit, weight of 100 grains of jatropha, dry weight and specific leaf area. Trimming by leaving 35 cm distance of the plant canopy growth and production yield a better distance than the pruning that leaves 25 cm and 15 cm distance of the plant canopy. Trimming by leaving 35 cm of the plant canopy distance produces the highest number of fruit harvested at 52 992 grams per plant. Correlation analysis showed a positive correlation between growth, production and plant physiology aspects of the distance.